Overexpression of Arabidopsis thaliana ERI, the homolog of C. elegans Enhancer of RNAinterference, leads to enhanced growth - Meyer, Rhonda C.; Hönig, Gunnar; Brandt, Ronny; Arana-Ceballos, Fernando; Neitsch, Cathleen; Reuter, Gunter; Altmann, Thomas; Kuhlmann, Markus (Frontiers in Plant Science, 2015)
Organisms adopt a wide range of strategies to adapt to change. Gene silencing describes the ability of organisms to modulate the expression of susceptible genes at certain times at the transcriptional or the translational level. In all known eukaryotic organisms 21-nucleotide long short interfering RNAs (siRNAs) are the effector molecules of post-transcriptional gene silencing, while 24-nucleotide long siRNAs are involved in transcriptional gene silencing in plants. Mutant studies in Caenorhabditis elegans lead to the identification of the enzyme ERI (Enhancer of RNAinterference) with enhanced post-transcriptional gene silencing. Although the genes involved in growth vigor and growth rate are still unknown, it becomes clearer that the population of small RNAs plays a role in the very early phase of plant development. To pinpoint the link between growth and siRNAs, the expression of Arabidopsis uni-gene Enhancer of RNAi (ERI) homolog from C.elegans was modulated. Increased degradation of small RNAs was achieved by ectopic AtERI overexpression in planta. Based on global small RNA analysis, AtERI overexpression affects mainly the population of 21mers, excluding miRNAs. To identify target genes, AtERI gain-of-function mutants were analyzed, and differentially abundant small RNAs were identified. Plants with an elevated level of AtERI were bigger in all three light intensities analyzed, indicating an inhibitory function of particular small RNAs in plant growth, with differences in RGRs depending on developmental stage and light intensity. Understanding the role of these siRNAs could open new avenues for enhancing plant growth.